A practical method for in-situ thickness determination using energy distribution of beta particles - Yalcin, S.; Gurler, O.; Gundogdu, O.; Bradley, Da (Elsevier BV, 2012)
This paper discusses a method to determine the thickness of an absorber using the energy distribution of beta particles. An empirical relationship was obtained between the absorber thickness and the energy distribution of beta particles transmitted through. The thickness of a polyethylene radioactive source cover was determined by exploiting this relationship, which has largely been left unexploited allowing us to determine the in-situ cover thickness of beta sources in a fast, cheap and non-destructive way.
Keywords: Equipment Failure Analysis; Energy Transfer; Skin Physiological Phenomena; Humans; Equipment Design; Radiometry; Sensitivity and Specificity; Beta Particles; Densitometry